2018
DOI: 10.3168/jds.2017-13859
|View full text |Cite
|
Sign up to set email alerts
|

Effects of repeated subacute ruminal acidosis challenges on the adaptation of the rumen bacterial community in Holstein bulls

Abstract: We investigated the effect of repeated subacute ruminal acidosis (SARA) challenges on the pH, fermentative function, and bacterial community in the rumen. Four rumen-cannulated Holstein bulls were fed a high-forage diet for 7 d (HF period) followed by a high-grain diet for 7 d (HG period). Four SARA challenges were carried out consecutively (first, second, third, and fourth challenges). The ruminal pH was measured continuously during the experiment, and rumen fluid samples during the first to fourth challenges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
36
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 39 publications
12
36
4
Order By: Relevance
“…The effect of the inoculum source was also observed in microbial diversity, suppporting the recent findings reported by Tapio et al [45] and Nagata et al [46] who showed the difference in the rumen microbial population when bulls were fed with forage or concentrate diets.…”
Section: Effect Of the Inoculum Source On The In Vitro Fermentation Psupporting
confidence: 83%
“…The effect of the inoculum source was also observed in microbial diversity, suppporting the recent findings reported by Tapio et al [45] and Nagata et al [46] who showed the difference in the rumen microbial population when bulls were fed with forage or concentrate diets.…”
Section: Effect Of the Inoculum Source On The In Vitro Fermentation Psupporting
confidence: 83%
“…However, the bacterial diversity (OTUs, PD whole tree, Chao1, and Shannon index) did not differ between the two periods or between the two groups, although the indices in both groups were lower during the HC period compared with the CON period. The reduction in rumen pH in the Mid group during the HC period was severe enough (6.00 to 5.76) to reduce bacterial diversity compared with a previous study (6.52 to 6.10 [15]). Therefore, we postulate that the rumen of the Japanese Black beef cattle adapted to long-term feeding of a high-concentrate diet to minimize the adverse changes in the bacterial diversity.…”
Section: Discussioncontrasting
confidence: 62%
“…Previously, Sato [21] suggested that feeding a high-concentrate diet can induce acidotic conditions via higher total VFA and lactic acid concentrations, which were consistent with the findings in our Late group. Although we could not fully explain the contrasting results between the middle and late fattening stages, the results suggest that the rumen is fully adapted to long-term acidic conditions during the late fattening stage, in line with a report that the rumen can adapt to SARA in Japanese Black cattle [15].…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Ingestion of these carbohydrates can lead to changes in the rumen pH, with prolonged reductions to values below 6.0. This new environment promotes the growth of amylolytic bacteria and inhibits the growth of cellulolytic bacteria, causing direct negative effects on digestibility (Nagata et al, 2018). On the other hand, rumen pH values below 5.8 increase the production of short-chain fatty acids (SCFA) and the proliferation of lactate-using bacteria (Bannink, France, & Lopez, 2008), making this value a threshold of vulnerability for the epithelium.…”
Section: Introductionmentioning
confidence: 99%